PENGARUH UKURAN PERUSAHAAN, LEVERAGE, LIKUIDITAS, PROFITABILITAS, DAN KINERJA LINGKUNGAN HIDUP TERHADAP PENGUNGKAPAN ISLAMIC SOCIAL REPORTING PADA PERUSAHAAN YANG TERDAFTAR DI JAKARTA ISLAMIC INDEX (JII) TAHUN 2012 â 2015 - Ratna Fauziyyah Age, 13.05.52.0154; Aini, Nur (Students Journal of Accounting and Banking, 2017)
This study aims to examine the effect of firm size, leverage, liquidity, profitability, and environmental performance on the disclosure of Islamic social reporting on companies listed in the Jakarta Islamic Index. The population in this study is a companies listed in the Jakarta Islamic Index during of the years 2012-2015. The sample in this study using purposive sampling method, so that the number of companies included in the sample criteria as many as 103 companies. The data analysis method used in this study is multiple linear regression analysis. The results showed that firm size variables have a significant positive effect on ISR disclosure. Leverage has a significant negative effect on ISR disclosure. Liquidity has a significant negative effect on ISR disclosure. Profitability has no significant negative effect. The environmental performance has negatively insignificant effect on ISR disclosure.Keywords: Islamic Social Reporting. firm Size. Leverage. Liquidity. Profitability. Environmental Performance